SORBS3-β suppresses lymph node metastasis in cervical cancer by promoting the ubiquitination of β-catenin - Huating Sun; Yinghui Zhang; Fang Wang; Zizhao Wang; Yuhong Zhang; Youguo Chen; Li Wang; Jinhua Zhou (Journal of Translational Medicine)
Abstract Background Cervical cancer (CC) is a prevalent gynecological malignancy, with lymph node metastasis (LNM) serving as a critical factor influencing patient prognosis. SORBS3, an adaptor protein with two known isoforms (α and β), has been implicated in tumor suppression, but the specific roles of its isoforms in CC metastasis remains unexplored. This study aimed to identify the functional isoform of SORBS3 driving LNM suppression and elucidate its mechanisms. Methods Proteomic analysis of clinical CC tissues and metastatic lymph nodes revealed progressive downregulation of SORBS3. The mRNA and protein levels of SORBS3-α and SORBS3-β were subsequently examined in normal cervical epithelial and CC cell lines. Functional studies, including siRNA-mediated knockdown of SORBS3-α, lentiviral-mediated overexpression and knockdown of SORBS3-β, Transwell migration, lymphangiogenesis assays, and in vivo footpad xenograft models, were conducted to evaluate the role of SORBS3 isoforms in LNM. SORBS3 DNA methylation mechanisms were analyzed by MSP and Targeted Bisulfite sequencing. Mechanistic insights were derived from Co-IP, ubiquitination assays, RNA-seq, and LC–MS/MS. Results Knockdown of SORBS3-α had no effect on CC cell migration, invasion, or lymphangiogenesis. In contrast, SORBS3-β overexpression markedly suppressed CC cell invasion, lymphangiogenesis, and adhesion to lymphatic endothelial cells, whereas its knockdown significantly promoted these phenotypes. Promoter hypermethylation driven by DNMT-1 inhibited SORBS3 expression in CC. SORBS3- β directly binds to β-catenin and recruits UBA1 to enhance its ubiquitination and degradation, thereby inhibiting Wnt/β-catenin signaling. This inhibition reduced accumulation of β-catenin and downregulated the pro-lymphangiogenic gene VEGFC, ultimately suppressing lymphangiogenesis and LNM. In vivo, SORBS3-β overexpression attenuated lymphatic metastasis in nude mice, whereas its knockdown promoted metastasis. Conclusion SORBS3-β is the major isoform of SORBS3 that inhibits lymphatic metastasis of cervical cancer by degrading β-catenin through UBA1-mediated ubiquitination, blocking Wnt/β-catenin signaling and downstream lymphangiogenesis pathways, thereby inhibiting lymphatic metastasis. Our findings elucidate key molecular mechanisms underlying cervical cancer lymph node metastasis, offering potential therapeutic targets.metastasis.